THE DOUBLE TRACK SYSTEM IN INDONESIAN CRIMINAL LAW: LEGAL RESPONSES TO CHILD SEXUAL ABUSE - atika, nur; Wahyu, (Muadalah : Jurnal Hukum, 2025)
Child sexual abuse constitutes a severe violation of human rights, causing multidimensional impacts—physically, psychologically, and socially. The rising number of such cases in Indonesia indicates that conventional sentencing systems have not been sufficiently effective in providing sustainable protection and deterrence. Therefore, Indonesia has adopted the double track system, a penal approach combining primary punishments such as imprisonment with additional measures like chemical castration, psychological rehabilitation, and the installation of electronic monitoring devices. This study aims to analyze the legal basis, effectiveness, and implementation challenges of the double track system in addressing child sexual crimes in Indonesia. Using a normative juridical method with a descriptive-analytical approach, the research draws on legal statutes, doctrinal studies, court rulings, and case analyses. The findings reveal that although regulatory frameworks exist, implementation still faces various obstacles, including inconsistencies in court decisions, resistance from medical professionals regarding chemical castration, and the limited availability of rehabilitation facilities. This study recommends the development of national technical guidelines, capacity building for law enforcement personnel, and harmonization between regulations and professional ethics to support a fair and effective implementation of the system.